(untitled) (Fiep Bulletin - online, 2015)
Plasma concentrations of creatine kinase (CK) has been used as an indicator of stress imposed due to skeletal muscle activity in various sports, seeking to identify the physical wear of athletes. However, there are few studies on the post-game that enzyme kinetics and a comparison with the wear of the competitive season football. The aim was to analyze the kinetics of CK concentration in sequential samples at different times before-game and post-game and their proper comparisons over time in a competitive game of the season without interrupting the schedule of trainings. Study participants were 12 professional soccer players (24.2 ± 3.1 years, 178 ± 5.0 cm, 10.5 ± 1.2% body fat and VO2 max 65.0 ± 4.5 ml / kg / min which participated in all pre-season and participated in at least 700 minutes of play). These were submitted to two moments collects a prior-game and a post-game Carioca Championship Serie B Professional. Plasma concentrations of CK showed the following values ??before CK-game (333.9 ± 195.9 UI.L-1), post-game (471.6 ± 244.3 UI.L-1) and the difference between two samples (137.6 ± 64.8 UI.L-1) and their respective standard deviations and Student’s t test (0.14). The comparison of CK before-game and post-game played with time during the season proved the correlation Person with Low Negative value of -0.19 and -0.28 respectively. It is concluded that the values ??of the plasma concentration of CK can measure the physical wear of athletes on a football season.